Semantic Data Markets: A Flexible Environment for Knowledge Management - de Virgilio, R; Orsi, G; Tanca, L; Torlone, R (2011)
We present Nyaya, a system for the management of Semantic-Web data which couples a general-purpose and extensible storage mechanism with efficient ontology reasoning and querying capabilities. Nyaya processes large Semantic-Web datasets, expressed in multiple formalisms, by transforming them into a collection of Semantic Data Kiosks. Nyaya uniformly exposes the native meta-data of each kiosk using the Datalog+/- language, a powerful rule-based modelling language for ontological databases. The kiosks form a Semantic Data Market where the data in each kiosk can be uniformly accessed using conjunctive queries and where users can specify user-defined constraints over the data. Nyaya is easily extensible and robust to updates of both data and meta-data in the kiosk and can readily adapt to different logical organization of the persistent storage. The approach has been experimented using well-known benchmarks, and compared to state-of-the-art research prototypes and commercial systems.